“They Treat You Like Some Alien” - Roshan Perry (Canadian Journal for the Academic Mind)
In moving towards liberatory healing for the trans-masculine community, it is imperative to understand their healthcare obstacles and the impact they have on the relationship between trans patients and the medical systems with which they interact. While there is little research on Indian transgender healthcare in general, scholarship about trans masculine experiences in routine, non-gender related healthcare is virtually non-existent. This study begins to fill this research gap with the central objective of understanding trans men and trans masculine people’s experiences in medicine and the barriers they face to general healthcare access in urban and suburban Mumbai. Through in-depth interviews with eight trans-masculine people and three healthcare providers in the Mumbai area, data showed that trans-masculine healthcare barriers presented much more in the public sector than the private. Several key health risks and barriers to care were found. Added health risks for trans-masculine participants include side effects of transition care, mental health challenges arising from stigma and dysphoria, and physical health demotivation and inaccessibility. Barriers to care include ignorance, (double) stigma, the risks of disclosure, and unaffordability. Participants discuss the individual and communal ways they navigate these spaces and propose solutions such as sensitization, more respectful care, and more awareness of trans people.